Development of a power factor correction buck converter in single phase rectifier using fuzzy logic - Muda@Othman, Asmawi (2013)
Power Factor Correction (PFC) circuits are widely used in single-phase rectifiers in order to emulate a linear resistive behavior. The buck PFC is still the most popular configuration due to its simplicity, but it suffers from high voltage stresses across the power electronic devices. This thesis presents to development buck converter in single phase rectifier used the fuzzy logic. The methodology integrates fuzzy logic controlling the output voltage of DC-DC converter and to improve performance of the buck converter during transient operation. Instead of generating fast pulse-width-modulated (PWM) signal, the digital signal processor is required to generate a slow- varying dc signal only for determining the PWM ramp function. A model for power factor correction has been formed by using the MALTAB software. The simulation and experimental results show that output voltage of buck converter can be control according to the value of duty cycle. The advantage of using the Buck Converter in power factor correction circuit is that better line regulation is obtained with appreciable power factor.